Mixed convection from a heat source in a channel with a porous insert: A numerical analysis based on local thermal non-equilibrium model. (1st October 2021) - Yerramalle, Vijayalakshmi; Premachandran, B.; Talukdar, Prabal
Highlights: Optimum thickness of porous insert is found to be equal to half the channel height. Porosity and particle diameter of porous insert govern the validity of LTE condition. Thermal conductivity, porosity and particle diameter govern the rate of heat transfer. The effect of buoyancy force at low Reynolds number is significant. Abstract: Numerical examination was carried out on mixed convection in a horizontal channel containing a single heat source at the bottom wall with a porous insert placed exactly on the heater surface. It was assumed that the porous insert partially fills the channel. The numerical simulations were carried out using the local thermal non-equilibrium (LTNE) condition and the temperature distribution of solid and fluid phases of porous insert were obtained. The impact of height of the porous insert, porosity of the porous insert, material and diameter of the solid particle of the porous insert, buoyancy force, Reynolds number of the flow on the distribution of temperature were investigated and the influence of these parameters over the applicability of the local thermal equilibrium condition (LTE) was also studied. The results indicate that the effect of buoyancy force is considerable and cannot be ignored at low Reynolds number. Applying the LTNE condition, the optimum thickness of porous insert for the improvement in heat transfer with a considerable pressure drop is found to be equal to half the channel height. The porosity of the porous insert, the particle diameter of the solid phase of the porous insert and the thermal conductivity of the solid phase of the porous insert highly affect the applicability of LTE condition.